The Philippine Star database on the internet an evaluation of precision capability - Ramos, Marielys Ann T. (1998)
The recent years have seen a massive information explosion, and with it a corresponding demand for faster access to more information. Since the introduction of the internet in the 1980s, people preferring to search online have increased exponentially over the last decade. Due to the proliferation of a wide variety of web sites, information has never been more accessible to the users.